Marked elevation of serum M2BP–adiponectin complex in men with coronary artery disease. (October 2016) - Niinaga, Ryu; Yamamoto, Hiroyasu; Yoshii, Manami; Uekita, Hiromi; Yamane, Noriko; Kochi, Ikoi; Matsumoto, Akane; Matsuoka, Tetsuro; Kihara, Shinji
Abstract: Background and aims: Adiponectin (APN) is an adipocyte-derived bioactive molecule with anti-diabetic and anti-atherogenic properties. Although the anti-diabetic effects of APN are mediated by AdipoR1 and AdipoR2, the anti-atherogenic mechanisms of APN remain unclear. The aim of this study was to determine the serum molecule inhibiting APN functions. Methods and results: By immunoprecipitation with an anti-APN antibody and mass spectrometry, we identified Mac-2 binding protein (M2BP) as a novel serum APN–binding protein. The association of M2BP and APN was confirmed using reconstituted proteins in vitro . Serum M2BP–APN complex levels were markedly higher in male patients with coronary artery disease (CAD) than in healthy subjects. M2BP abrogated the suppressive effects of APN on tumour necrosis factor (TNF)-α−induced inflammation in vascular endothelial cells. Conclusions: The increment of serum M2BP–APN complex could be a novel risk factor for CAD, through the abolishment of the anti-atherogenic effects of APN. Highlights: Mac-2 binding protein (M2BP) is a novel serum adiponectin (APN)-binding protein. Serum levels of M2BP-APN complex are elevated in coronary artery disease (CAD). Anti-inflammatory properties of APN are abrogated by M2BP.